Key success factors on loyalty of festival visitors: the mediating effect of festival experience and festival image - Dalgiç, Ali (2020)
This study, based on systems theory, information processing theory, image theory, stimulus-organism-response theory and reasoned action theory, was conducted on festival visitors to investigate festival key success factors' effect on festival experience, festival image and festival loyalty. In addition, the effect of key success factors on festival loyalty through the mediator role of festival experience and festival image was investigated. This research developed a model by bringing together festival key success factors, festival experience (emotional and cognitive experience), festival image (emotional and cognitive experience) and festival loyalty. Study data were gathered from participants joining Orange Blossom Festival. Path analysis and structural equation modelling analysis showed that festival key success factors, festival experience and festival image variables have significant and positive effect on festival loyalty. Moreover, it was revealed that festival experience and festival image play a mediating role on effect of festival key success factors on festival loyalty.